Who Shape the City? Non-profit associations and civil society initiatives in urban change processes: role and ambivalences - Magda Bolzoni (Coordinamento SIBA, 2019)
The present paper focuses on non-profit sector and civil society initiatives within urban change processes. More specifically, it looks into experiences that are characterised by a local/area-based ap-proach and that arise in relation, response and reaction to the processes of city change, becoming and be-ing recognised as one of its actors. By examining different initiatives variously involved in the regeneration process of a semi-central neighbourhood of the city of Torino (Italy), and by investigating their origins, goals and actions, the paper addresses the transformations that they go through over time, their complex relation with other local actors, and their role in the regeneration process, overall pointing out the different forms of ambiguity and ambivalences that they bear.